Quality assessment of chicken meatball with different types of antioxidants in short-term preservation - Biplob, MAKA; Hossan, MI; Khatun, H; Rahman, MM (Meat Research, 2024)
This study evaluated the effect of natural antioxidants—lemon (Citrus limon) extract, tulsi (Ocimum tenuiflorum) extract, and moringa (Moringa oleifera Lam.) extract—on the quality of chicken meatballs. Samples were divided into four groups: T0 (control), T1 (0.5% lemon extract), T2 (0.5% tulsi extract), and T3 (0.5% moringa extract). Stored at 4°C for 12 days, they were analyzed at 0, 4, 8, and 12 days for sensory, proximate, physicochemical, biochemical, and microbiological properties. T1 had the best color, flavor, and tenderness, while T3 showed the least preferable values. Sensory attributes declined over time but remained acceptable. T3 had the highest dry matter (DM) content, while T0 had the lowest. Crude protein (CP) was highest in T1 and lowest in T3 . Ether extract (EE) decreased across all treatments, reaching 3.15% by day 12. Ash content increased to 1.43% but remained within acceptable limits. Cooked pH was most stable in T1 and T2 , slightly decreasing over time due to increased acidity. Cooking loss was lowest in T2 , indicating better retention of moisture and nutrients. Thiobarbituric acid reactive substances (TBARS) values, indicating lipid oxidation, were lowest in T1 and increased over storage. Microbial analysis showed T0 had the highest total viable count (TVC, 5.14 log CFU/g), while T1 had the lowest. Total coliform count (TCC) and total yeast-mold count (TYMC) were also highest in T0 , decreasing significantly in antioxidant-treated samples. Overall, T1 (0.5% lemon extract) was the most effective in improving sensory, biochemical, and microbial quality. Therefore, lemon extract can enhance chicken meatball quality and shelf life as a natural antioxidant.